The Meaning of Environmental Accountability in Daily Practice: A Phenomenological Study of Cleaning Officers - Khairum Nadila Sandy; Lilis Karfina Ar; Darwis Said; Alimuddin Alimuddin (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to explore the meaning of environmental accountability based on the lived experiences of janitorial staff at Hasanuddin University using an interpretive phenomenological approach. Environmental accountability in higher education has generally been understood through formal policies, reporting systems, and green campus programs, while the experiences of frontline actors who maintain environmental sustainability on a daily basis remain underexplored. Through in-depth interviews, observations, and documentation, this research examines how janitors construct ecological awareness, moral responsibility, and the personal meaning of their work. The findings reveal that environmental accountability is understood as a moral, social, and spiritual responsibility. Janitors perceive campus cleanliness as an act of worship, stewardship, and a contribution to environmental preservation. Local Bugis-Makassar cultural values sipakatau, siri' na pacce, and sipakainge strongly shape their work ethics and collective sense of responsibility. The study also identifies a gap between formal environmental accountability and lived experience, as janitors are not significantly involved in campus sustainability policymaking despite their vital operational role. This research highlights that environmental accountability is phenomenological, moral, and cultural in nature. It suggests the need for a more inclusive accountability model grounded in the lived experiences of frontline environmental actors.